I know that I know nothing: Cortical thickness and functional connectivity underlying meta-ignorance ability in pre-schoolers. (February 2020) - Filevich, Elisa; Forlim, Caroline Garcia; Fehrman, Carmen; Forster, Carina; Paulus, Markus; Shing, Yee Lee; Kühn, Simone
Highlights: At five years old, we start to be able to report that we do not know something. Cortical thickness in mOFC linked to childrens' ability to report their ignorance. This region was functionally connected to parts of the default-mode network. The default-mode network might support the development of metacognitive ability. Abstract: Metacognition plays a pivotal role in human development. The ability to realize that we do not know something, or meta-ignorance, emerges after approximately five years of age. We sought for the brain systems that underlie the developmental emergence of this ability in a preschool sample. Twenty-four children aged between five and six years answered questions under three conditions. In the critical partial knowledge condition, an experimenter first showed two toys to a child, then announced that she would place one of them in a box, out of sight from the child. The experimenter then asked the child whether she knew which toy was in the box. Children who gave consistently correct answers to this question (n = 9) showed greater cortical thickness in a cluster within left medial orbitofrontal cortex than children who did not (n = 15). Further, seed-based functional connectivity analyses of the brain during resting state revealed that this region is functionally connected to the medial orbitofrontal gyrus, posterior cingulate gyrus and precuneus, and mid- and inferior temporal gyri. This finding suggests that the default mode network, critically through its prefrontal regions, supports introspective processing. It leads to the emergence of metacognitive monitoring allowing children to explicitly report their own ignorance.